Hazardous seascapes for marine turtles in the Mediterranean sea - G. Quattrocchi; G. Cilluffo; G. Buffa; A. Camedda; A. Cucco; G.A. De Lucia; R. Disclafani; G. Schirò; R. Sorgente; S. Vizzini; G. Signa (Environmental Pollution, 2026)

Mediterranean developed coasts: what future for the foredune restoration? - A. Della Bella; E. Fantinato; F. Scarton; G. Buffa (Journal of Coastal Conservation, 2021)
The feasibility and efficacy of soft engineering foredune restoration approaches still lack insight from research and monitoring activities, especially in areas where dunes are under persisting human disturbance. We evaluated the efficacy of Mediterranean foredune restoration in dune areas freely accessible to tourists. Foredunes were reconstructed using only sand already available at nearby places and consolidated through the plantation of seedlings of native ecosystem engineer species and foredune focal species. We monitored transplanted and spontaneous seedlings for one year to assess their mortality and growth in relation to the distance from the closest beach access, either formal or informal, as proxy of human disturbance. We also tested whether species differing in their ecology (i.e., affinity to a given habitat) and growth form showed different response to human disturbance. The relationship between seedling mortality and growth and the distance from the closest beach access was tested through Generalized Linear Mixed Models. We found a clear spatial pattern of seedling survival and growth, which decreased as the proximity to the closest beach access increased. Only invasive alien plants and erect leafy species showed to better perform at lower distances from beach accesses. In dune areas with a strong tourist vocation, foredune restoration should be coupled with the implementation of integrated management plans aiming at optimising the relationship between protection and use. Management plans should not only rely on passive conservation measures; rather they should include educational activities to stimulate a pro-environmental behaviour, increase the acceptance of behaviour rules and no entry zones, and actively engage stakeholders in long-term conservation.

Anchovy (Engraulis encrasicolus) early life stages in the Central Mediterranean Sea: connectivity issues emerging among adjacent sub-areas across the Strait of Sicily - B. Patti; R. Zarrad; O. Jarboui; A. Cuttitta; G. Basilone; S. Aronica; F. Placenti; G. Tranchida; G. M. Armeri; G. Buffa; R. Ferreri; S. Genovese; et al. (Hydrobiologia, 2018)

Habitat conservation in Italy: the state of the art in the light of the first European Red List of Terrestrial and Freshwater Habitats - D. Gigante; A. T. R. Acosta; E. Agrillo; S. Armiraglio; S. Assini; F. Attorre; S. Bagella; G. Buffa; L. Casella; C. Giancola; G. P. Giusso del Galdo; C. Marcenò; et al. (Rendiconti Lincei. Scienze Fisiche e Naturali, 2018)

Distribution map of Ambrosia artemisiifolia L. (Asteraceae) in Italy - R. Gentili; F. Gilardelli; E. Bona; F. Prosser; A. Selvaggi; A. Alessandrini; F. Martini; P. L. Nimis; T. Wilhalm; M. Adorni; N. M. G. Ardenghi; E. Barni; et al. (Plant Biosystems, 2017)

Trace element concentrations in red swamp crayfish (Procambarus clarkii) and surface sediments in Lake Preola and Gorghi Tondi natural reserve, SW Sicily - A. Bellante; V. Maccarone; G. Buscaino; G. Buffa; F. Filiciotto; A. Traina; M. Del Core; S. Mazzola; M. Sprovieri (Environmental Monitoring and Assessment, 2015)

Are the ancient forests of the Eastern Po Plain large enough for a long term conservation of herbaceous nemoral species? - G. Buffa; M. Villani (Plant Biosystems, 2012)

Correlations among biodiversity, biomass and other plant community parameters using the phytosociological approach: A case study from the south-eastern Alps - L. Poldini; G. Sburlino; G. Buffa; M. Vidali (Plant Biosystems, 2011)

Phytocoenotic originality of the N-Adriatic coastal sand dunes (Northern Italy) in the European context: The Stipa veneta -rich communities - G. Sburlino; G. Buffa; L. Filesi; U. Gamper (Plant Biosystems, 2008)

N,N-dicarboxymethyl chitosan as delivery agent for bone morphogenetic protein in the repair of articular cartilage - M. Mattioli-Belmonte; A. Gigante; R. A. A. Muzzarelli; R. Politano; A. De Benedittis; N. Specchia; A. Buffa; G. Biagini; F. Greco (Medical & Biological Engineering & Computing, 1999)